The Viewpoint of The Young Muhammadiyah Intellectuals towards The Religious Minority Groups in Indonesia - Arifin, Syamsul; Muthohirin, Nafik (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2019)
Muhammadiyah keeps onto make a positive contribution to the progress of Indonesia. In the first century of its advent, Muhammadiyah focused on advancing education, health, and compensation to the du?af?, while through the 47th Congress in Makassar (2015), Muhammadiyah had issued an important point which emphasizes on the minority groups. This article examines a number of issues dealing with the views that underlie young Muhammadiyah intellectuals in voicing partiality towards the religious minority, the role or form of alignments and the implications of these views on thought upheavals within Muhammadiyah internally and at the national level. The study finds that the young Muhammadiyah intellectuals play a pivotal role in fighting for the basic rights of a religious minority which continues to face the complicated problem of citizenship. The data has been focused on advocacy and intellectual works, including a literature review of statements of attitudes, published books, journals, research reports, and opinions in the national mainstream and alternative media.